2017
DOI: 10.1093/geroni/igx007
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hospital Admission Risk Profile Score with Mortality in Hospitalized Older Adults

Abstract: ObjectivesTo evaluate the association of the Hospital Admission Risk Profile (HARP) score with mortality after discharge in a population of hospitalized older adults.DesignRetrospective cohort study.ParticipantsHospitalized patients aged 70 years or older.MeasurementsPatient age at the time of admission, modified Folstein Mini-Mental Status Exam score, and self-reported instrumental activities of daily living 2 weeks prior to admission were used to calculate a HARP score. The primary outcome assessed was overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
2
Order By: Relevance
“…In fully adjusted Cox proportional models, mortality odds in those patients was 3.5 times higher compared to patients with low HARP scores. This finding suggests that HARP allows for identifying patients with a high risk of hospital-associated functional decline and mortality after discharge 22 . In addition, the same authors reported that the scale measured at admission could identify patients with a higher risk of requiring a skilled nursing or acute rehabilitation facility at discharge.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In fully adjusted Cox proportional models, mortality odds in those patients was 3.5 times higher compared to patients with low HARP scores. This finding suggests that HARP allows for identifying patients with a high risk of hospital-associated functional decline and mortality after discharge 22 . In addition, the same authors reported that the scale measured at admission could identify patients with a higher risk of requiring a skilled nursing or acute rehabilitation facility at discharge.…”
Section: Discussionmentioning
confidence: 73%
“…En modelos proporcionales de Cox ajustados, la probabilidad de mortalidad en esos pacientes fue 3.5 veces mayor en comparación con los pacientes con puntajes HARP bajos. Este hallazgo sugiere que la escala HARP permite identificar pacientes con alto riesgo de deterioro funcional hospitalario y mortalidad después del alta 22 . Además, los mismos autores informaron que la escala medida al ingreso podría identificar a los pacientes con mayor riesgo de requerir una unidad de enfermería especializada o de rehabilitación aguda al alta.…”
Section: Discussionunclassified
“…В настоящее время не вызывает сомнения, что ре шающая роль в прогрессировании, госпитализации и смерти больных ХОБЛ принадлежит обострениям [6,7] При этом среди множества причин обострений на пер вом месте находится воздействие инфекционного фак тора [8]. Наряду с этим имеют значение снижение ле гочной функции, влияние аэрополлютантов, слабая приверженность к поддерживающей фармакотерапии, декомпенсация сопутствующих заболеваний (прежде всего, сердечнососудистой патологии) [6,[9][10][11].…”
Section: Introductionunclassified
“…(5) , (6) , (7) , (8) , (9) However, performance-based functional assessments to assess CKD outcomes have been inadequately studied. (10) Previous reports indicate performance on many performance-based functional assessments is linked to survival in numerous disease populations (11) , (12), but to our knowledge the association of performance-based functional assessments with outcomes in CKD patients, including ESKD and death, have not been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%